2018
DOI: 10.1088/1748-3190/aaac53
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired wingtip devices: a pathway to improve aerodynamic performance during low Reynolds number flight

Abstract: Birds are highly capable and maneuverable fliers, traits not currently shared with current small unmanned aerial vehicles. They are able to achieve these flight capabilities by adapting the shape of their wings during flight in a variety of complex manners. One feature of bird wings, the primary feathers, separate to form wingtip gaps at the distal end of the wing. This paper presents bio-inspired wingtip devices with varying wingtip gap sizes, defined as the chordwise distance between wingtip devices, for ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…24 C L versus C D for the planar configuration demon-strating the effect of gap size. γ = 20% produces the greatest lift while incurring small drag penalties for the wing-wingtip system [33] Fig. 25 C Di versus α b for planar and nonplanar configurations for pre-stall angles of attack showing a reduction in induced drag when switching to a nonplanar configuration [33] showed that the tip sails have observable efficiency in reducing induced drag.…”
Section: Engineering Applications Of Wingtip Slotsmentioning
confidence: 98%
See 3 more Smart Citations
“…24 C L versus C D for the planar configuration demon-strating the effect of gap size. γ = 20% produces the greatest lift while incurring small drag penalties for the wing-wingtip system [33] Fig. 25 C Di versus α b for planar and nonplanar configurations for pre-stall angles of attack showing a reduction in induced drag when switching to a nonplanar configuration [33] showed that the tip sails have observable efficiency in reducing induced drag.…”
Section: Engineering Applications Of Wingtip Slotsmentioning
confidence: 98%
“…γ = 20% produces the greatest lift while incurring small drag penalties for the wing-wingtip system [33] Fig. 25 C Di versus α b for planar and nonplanar configurations for pre-stall angles of attack showing a reduction in induced drag when switching to a nonplanar configuration [33] showed that the tip sails have observable efficiency in reducing induced drag. To study the potential use of adaptive wingtip sails for the reduction of induced drag through variations of cant angles, a total of 55 configurations were chosen with different cant angles by Cerón-Muñoz et al [47,48] and tested their performance in a wind tunnel (Figs.…”
Section: Engineering Applications Of Wingtip Slotsmentioning
confidence: 98%
See 2 more Smart Citations
“…Due to the rapid emergence of unmanned air vehicles, the aerodynamic characteristics of wing-tip vortices of small scale aircraft have extensively been investigated. Lynch et al (2018) tested the aerodynamic performance of a bioinspired wing-tip, which is a wing-tip with gaps mimicking a wing of a bald eagle. They reported improvements in lift and drag characteristics versus the conventional wing-tip.…”
Section: Introductionmentioning
confidence: 99%